Enhanced and persistent antibody response against homologous and heterologous strains elicited by a MF59®-adjuvanted influenza vaccine in infants and young children - Nolan, Terry; Bravo, Lulu; Ceballos, Ana; Mitha, Essack; Gray, Glenda; Quiambao, Beatriz; Patel, Sanjay S.; Bizjajeva, Svetlana; Bock, Hans; Nazaire-Bermal, Nancy; Forleo-Neto, Eduardo; Cioppa, Giovanni Della; et al. (Vaccine, 2014)
•Adjuvanted (aTIV) and two non-adjuvanted (TIV) vaccines compared in young children.•Enhanced antibody response to aTIV against all homologous and heterologous strains.•Significantly faster (after one dose) and more persistent response to aTIV.•aTIV increasingly superior to TIV with increasing HI threshold titer.•Higher reactogenicity of aTIV, offset by increased immunogenicity. Non-adjuvanted seasonal influenza vaccines show only modest efficacy in young children. This study compared the immunogenicity, reactogenicity and safety of the MF59®-adjuvanted trivalent subunit vaccine (aTIV) with two non-adjuvanted trivalent vaccines, TIV-1, the non-adjuvanted version of aTIV, and TIV-2, a split virion vaccine. 6078 children received two doses of aTIV (n=3125), TIV-1 (n=1479), or TIV-2 (n=1474) four weeks apart (Days 1 and 29). Children aged 6 to <36 months and 36 to <72 months received 0.25mL and 0.50mL doses, respectively. Immunogenicity was assessed by hemagglutination inhibition (HI) assay (n=2435) on Days 1, 29, 50 and 209. Safety was assessed up to Day 394. After the second vaccination (Day 50), the aTIV group showed significantly higher geometric mean HI titers and seroconversion rates than the TIV-1 or TIV-2 groups against all homologous and heterologous strains. The difference was enhanced at HI titers ≥110. aTIV elicited a faster, more persistent antibody response, with significantly higher titers in the aTIV group after one vaccination (Day 29) and after six months (Day 209) than in either TIV group. aTIV was more reactogenic than were TIV-1 and TIV-2 but rates of severe adverse events were very low for all three vaccines. In infants and young children, the MF59-adjuvanted vaccine induced substantially faster (after one dose), higher, persistent HI titers than the non-adjuvanted vaccines, with consistently higher seroprotection rates at increased threshold HI titers. This trial is registered at clinicaltrials.gov: NCT01346592.